1970
DOI: 10.3329/jbau.v7i1.4978
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mud crab (<i>Scylla serrata</i>) fattening practices between two different systems in Bangladesh

Abstract: A study was conducted to compare the survival, production and economics of mud crab fattening in cage with fattening in encircled earthen brackishwater pond. Thirty cages of 1m (L) × 1m (W) × 0.3m (H) partitioned into 16 compartments (each 25 × 25 × 30 cm) were set in a 40 m 2 pond and another pond with same area was encircled with bamboo fence. Mud crab fattening in cage and in encircled earthen area were considered as Treatment-1 and Treatment-2, respectively with three replications each to compare the fatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 1 publication
0
26
1
1
Order By: Relevance
“…Our earlier results have shown the positive effect of dry pellet form of feeding compared with other physical forms of presentation (Ali et al, ). The growth recorded in the present study is higher than that reported in an earlier fattening demonstration in cage and pond (Begum et al, ), and this could possibly be attributed to the size of the crabs used for the experiment, diet and also the rearing system. The balancing of essential amino acids is crucial as per the requirement of the species and stage of growth.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our earlier results have shown the positive effect of dry pellet form of feeding compared with other physical forms of presentation (Ali et al, ). The growth recorded in the present study is higher than that reported in an earlier fattening demonstration in cage and pond (Begum et al, ), and this could possibly be attributed to the size of the crabs used for the experiment, diet and also the rearing system. The balancing of essential amino acids is crucial as per the requirement of the species and stage of growth.…”
Section: Discussioncontrasting
confidence: 82%
“…The process of rearing these soft crabs until they are “full” and ready for market is called “fattening.” In the wild fishery, approximately 7%–10% of the catch on an average are soft crabs and are usually low priced, but these crabs when fattened for a month to a “full” hard crab increase their average value by over 200%; hence, this can be regarded both as a product improvement technique and as a specific type of value‐added aquaculture (Patterson & Samuel, ). The fattening experiments in ponds and cages have indicated lower survival in ponds due to cannibalism and escape because of the burrowing habit of mud crabs (Begum, Shah, Mamun, & Alam, ). In most of the earlier mud crab farming demonstration trials in Asia and Africa, trash fish, clam meat or animal by‐products have been used as feeds (Mirera & Mtile, ).…”
Section: Introductionmentioning
confidence: 99%
“…The mud crab ( Scylla serrata ), a commercially important shellfish with considerable global demand is highly perishable especially during their transportation away from the place of catch (Begum et al . ; Lalitha and Nirmala ). However, to date, no reports are available on the effect of irradiation or cold storage on the bacteriological quality of this shellfish species.…”
Section: Introductionmentioning
confidence: 98%
“…Juliette (2010) reported that in the Philippines the mud crab represents between 20 and 30% of the value of the production against 20 -50% for the shrimp (Salam et al 2002). Crab fattening is widely practiced in Thailand, Taiwan, Malaysia, Singapore, India, Indonesia and Bangladesh (Begum 2009). According to Sudhakar (2009) and Yousuf et al (2017) mud crab has been well-accepted as a good source of protein and antioxidant properties, scrumptious and demandable crustacean in the world.…”
Section: Introductionmentioning
confidence: 99%